Apomictic lines of sugar beet: development and studying - D. V. Sokolova (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. While working with such cross-pollinated crops as sugar beet, the greatest problem is the fixation of valuable genotypes. Using apomixis to produce breeding material helps to accelerate the breeding process and save the desired combination of genes.Materials and methods. The research objects were 110 accessions of sugar beet from the VIR collection. Field experiments and assessments of the resistance to Cercospora leaf spot, monogermity, and non-bolting were performed according to VIR’s guidelines in 2016–2018 at Pushkin and Pavlovsk Laboratories of VIR and Maikop Experiment Station of VIR. The sugar level in roots was measured using an optical refractometer.Results. A comprehensive study of sugar beet accessions resulted in the development of apomictic lines with cytoplasmic male sterility, followed by an evaluation of their economically important characters. An extremely rare occurrence of biotypes with the 0-type sterility (less than 0.5%) was observed in the population. The seeds obtained from apomixis-prone lines demonstrated a significant difference during inbreeding from the seeds of fertile inbred genotypes: no inbreeding depression was observed in apomictic lines. Lines combining sterility and monogermity in their genotype were produced. Testing parent accessions and apomictic forms did not reveal significant differences in the sugar content and root yield, so the resulting forms can be efficiently used in future breeding programs.Conclusion. Using apomixis to develop sugar beet lines helped to fixate the sugar content level, biennial plant development cycle, and Cercospora leaf spot resistance. Thus, apomixis is promising for ensuring maternal inheritance and preserving the desired combination of genes in sugar beet, thereby accelerating the breeding process.